Efecto de la temperatura y concentración microbiana de bacillus sp. en la degradación de grasas de agua residual de curtiembre Quimipiel S.A.C. - Vergara Polo, Karol America (2018)
In the present investigation the influence of the temperature and microbial concentration of Bacillus sp. on the biodegradation of fats and oils from the wastewater of Tanneries - Rolemt. in the riverside stage. The Bacillus sp. strain was isolated and identified of the grease trap of a chicken. The tests for the biodegradation of commercial oil were carried out, with a bifactorial design of three levels with three repetitions: temperatures of 25 °C, 30 °C and 35 °C; and cellular concentrations of 1.5 x 108, 3x108 and 6x108 CFU/ml. obtaining the optimum conditions of 35 °C temperature and 6x108 CFU/ml. of bacterial concentration at 72 hours of incubation. In the Treatment of the residual water of tannery, it was possible to remove the fat at 100%, since its maximum concentration was 4549 ppm. and the dosage was ready to degrade 50,000 ppm